Minimally invasive McKeown esophagectomy with two-field lymph node dissection and manual cervical esophagogastric anastomosis - Lv, Fang; Zhang, Fan; Wang, Zheng; Gao, Shugeng (Journal of Thoracic Disease, 2019)
Since McKeown first described his esophagectomy in 1978 (1), this three-field surgery has been widely applied in clinical practice, and particularly gained momentum when the “minimally invasive era” began in the early 1990s (2). This procedure is now the mainstream esophagectomy pattern for esophageal cancer [over 90% of total procedures (3)] because (I) it can achieve en bloc resection of both thoracic and gastric lymph nodes, and (II) the cervical anastomotic leaks can be opened and drained very conveniently (4). However, the entirety of the McKeown esophagectomy procedure is still challenging for some surgeons due to its long surgical duration (~480 minutes), complicated surgical steps, and relatively high anastomotic leak rate (5). Here, we present a case of minimally invasive McKeown esophagectomy with en bloc lymph node dissection and manual anastomosis for a male with squamous cell carcinoma in the inferior esophagus.